Theoretical and Practical Challenges in Assessing Intercultural Competence - Lyu, Xinxin (International Journal of Social Sciences and Public Administration, 2024)
Assessing intercultural competence is crucial in today's globalized business landscape. This study delves into the challenges of evaluating intercultural competence, focusing on dimensions like cultural understanding, adaptability, sensitivity, and intercultural interaction. By exploring theoretical frameworks and practical hurdles in assessing intercultural competence, the research aims to illuminate its evaluation across disciplinary contexts. Additionally, the study aims to elevate understanding of cultural differences, trust-building, effective communication, efficiency enhancement, and innovation fostering. It also seeks to offer comparative methods for evaluating dynamic intercultural competences at different learning stages and provide insights to enhance professional communication in diverse business settings. The study underscores the significance of creating inclusive assessment tools adaptable to diverse disciplinary contexts, with findings expected to provide valuable guidance for individuals navigating cultural differences in diverse and multicultural business settings.